Coal demand, market forces, and U.S. coal mine closures. (1st July 2022) - Watson, Brett; Lange, Ian; Linn, Joshua
Abstract: Economic transitions have the potential to displace workers and cause social unrest. Coal mine closures and the resulting employment losses in rural areas have become salient issues. Using data on coal mine and power plant operation, we model closure as a function of expected profits, which allows us to compare the effects on mine closure of specific demand and supply shocks to expected mine profits. Increasing costs of production have had a large impact on closures, but lower natural gas prices and lower electricity demand have played more recently important roles.